(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This research will explore the contribution of the Shanghai Cooperation Organization (SCO) to security integration in Central Asia and its limiting factors. The period of defining the topic used theory of international relations realism and institutionalism. Within research activity of RATS, friendly military actions and diplomatic intercessions are highly rated, but something discovered in research that institutional weakness and different incomes of every country stopped the integrity of